2017
DOI: 10.1017/ice.2016.327
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Ralstonia pickettii Bloodstream Infection Associated with an Intrinsically Contaminated Normal Saline Solution

Abstract: OBJECTIVERalstonia pickettii has caused contamination of pharmaceutical solutions in many countries, resulting in healthcare infections or outbreak events. We determined the source of the outbreak of R. pickettii bloodstream infection (BSI).METHODSThis study was conducted in a 3,000-bed tertiary referral medical center in Taiwan with >8,500 admissions during May 2015. Patients had been treated in the injection room or chemotherapy room at outpatient departments, emergency department, or hospital wards. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…One possibility is that the infection was acquired following contamination during or after the neurosurgical clipping procedure. Indeed, Ralstonia bacteria have been associated with infections in hospital settings due to their ability to survive in liquid media (including saline and chlorhexidine with 0.05% aqueous solutions) and on hospital devices 19. In our case, environmental samples of air or from inanimate surfaces taken monthly in the operating rooms and in all areas where the patient had been treated were negative for Ralstonia spp; this is not surprising as even in cases of well documented hospital outbreaks the environmental origin was not identified 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the infection was acquired following contamination during or after the neurosurgical clipping procedure. Indeed, Ralstonia bacteria have been associated with infections in hospital settings due to their ability to survive in liquid media (including saline and chlorhexidine with 0.05% aqueous solutions) and on hospital devices 19. In our case, environmental samples of air or from inanimate surfaces taken monthly in the operating rooms and in all areas where the patient had been treated were negative for Ralstonia spp; this is not surprising as even in cases of well documented hospital outbreaks the environmental origin was not identified 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen is now commonly recognized and implicated in septicemia in immunocompromised and debilitated hospitalized patients . Outbreaks have occurred due to contaminated solutions causing respiratory illnesses, endopthalmitis, otitis media, meningitis, prosthetic joint infections, and nonspecific bacteremic symptoms …”
Section: Discussionmentioning
confidence: 99%
“…18 Outbreaks have occurred due to contaminated solutions causing respiratory illnesses, 23 endopthalmitis, 12 otitis media, 24 meningitis, 25 prosthetic joint infections, 26 and nonspecific bacteremic symptoms. 3,4,27 A case of S. maltophilia infection in a hemodialysis patient with a tunneled central venous catheter which did not respond to ceftazidime and ciprofloxacin. Long-term daily locked-in therapy with ceftazidime was able to save both the catheter and the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, several studies from multiple countries reported cases caused by pharmaceutical solutions. 9,10 In our case, we performed surveillance cultures from the hospital water sources, sterilization chemicals, water-based solutions, medication bottles, respiratory therapy equipment, and specimens from baby incubator to try to find the source of infection. Surveillance cultures were all negative; there were no additional cases of Ralstonia spp.…”
Section: Discussionmentioning
confidence: 99%